# |
ODE |
Mathematica |
Maple |
\[
{}2 y y^{\prime \prime \prime }+2 \left (y+3 y^{\prime }\right ) y^{\prime \prime }+2 {y^{\prime }}^{2} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+2 y+3 y^{2}\right ) y^{\prime \prime \prime }+6 y^{\prime } \left (y^{\prime \prime }+{y^{\prime }}^{2}+3 y^{\prime \prime } y\right ) = x
\] |
✓ |
✓ |
|
\[
{}3 x \left (y^{2} y^{\prime \prime \prime }+6 y y^{\prime } y^{\prime \prime }+2 {y^{\prime }}^{3}\right )-3 y \left (y^{\prime \prime } y+2 {y^{\prime }}^{2}\right ) = -\frac {2}{x}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime \prime }+3 y^{\prime } y^{\prime \prime }-2 y^{\prime \prime } y-2 {y^{\prime }}^{2}+y y^{\prime } = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime } y-{y^{\prime }}^{2}+1 = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime \prime \prime }+x y^{\prime \prime }+\left (2 x y-1\right ) y^{\prime }+y^{2}-f \left (x \right ) = 0
\] |
✗ |
✗ |
|
\[
{}\left (x y^{\prime \prime \prime }-y^{\prime \prime }\right )^{2} = {y^{\prime \prime \prime }}^{2}+1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime \prime }}^{2}+{y^{\prime \prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y y^{\prime \prime \prime \prime } = 1
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }+x y^{\prime \prime }-y^{2} = \sin \left (x \right )
\] |
✗ |
✗ |
|
\[
{}\sin \left (y^{\prime \prime }\right )+y y^{\prime \prime \prime \prime } = 1
\] |
✗ |
✗ |
|
\[
{}{y^{\prime \prime \prime }}^{2}+\sqrt {y} = \sin \left (x \right )
\] |
✗ |
✗ |
|
\[
{}2 x y^{\prime \prime \prime } y^{\prime \prime } = {y^{\prime \prime }}^{2}-a^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y^{\prime \prime \prime } = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y^{\prime \prime \prime } = 2
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime \prime } y^{\prime \prime } = {y^{\prime \prime }}^{2}-a^{2}
\] |
✓ |
✓ |
|